Penanaman Mangrove di Pesisir Pantai Sulamanda bersama Karang Taruna dan Masyarakat Desa Mata Air: Mangrove planting on the coast of Sulamanda Beach with Karang Taruna and the Mata Air Village Community - Saraswati, Suprabadevi Ayumayasari Saraswati; Christian Liufeto, Franchy; Pasaribu, Wesly; Hanifah, Ahmad (Program Studi Budidaya Perairan Universitas Mataram, 2023)
The mangrove ecosystem in the Sulamanda village plays an important role for the lives of the surrounding community. The management and utilization of mangrove ecosystems by local communities tends to lead to areas that protect people's homes from waves and high tides. Therefore it is important for us to carry out nurseries and care for mangrove seedlings so that they can replant them in their natural habitat in good condition and grow well. This nursery service will be held in September 2021 at Sulamada Beach, Kupang. Dean of the Faculty of Maritime Affairs and Fisheries (FKP) Dr. Franchy Ch. Liufeto, S.Pi., M.Sc, with the Head of Karang Taruna Ari Buraen and the Head of Mata Air Beni Kanuk Village. Collaborating in an effort to carry out activities for planting 500 mangrove saplings, which involved Marine and Fisheries Faculty Students and Youth from Karang Taruna and Mata Air Village. This activity was carried out on September 23, 2021. In a short presentation, Dr. Franchy stated that the beach which had been damaged by abrasion had to be rehabilitated by planting mangrove seedlings. To support these activities, his party will provide assistance to village officials and youth organizations to continue to maintain the survival of mangrove seedlings. This was welcomed by the youth organization and the local village community. There are several beaches in NTT that can protect residential areas from abrasion, such as Sulamanda Beach which is located in Mata Air Village, Central Kupang District, Kupang Regency. However, it has suffered damage due to beach abrasion. This has received special attention from several parties, such as the Karang Taruna Faculty of Marine Affairs and Fisheries (FKP) and residents of Mata Air Village who are in that location. Mangrove restoration activities, from seeding to monitoring, are one of the efforts to protect the mangrove ecosystem.